THE SEVERITY OF COVID-19 IS ASSESSED FROM D-DIMER AND PLATELET LEVELS - Putra, Catur Permana; Basuki, Sri Wahyu; Mahmuda, Iin Novita Nurhidayati; Dwi, Raafika Studiviani (Indonesian Journal of Health Science, 2024)
This research was conducted with purpose to analyse the association between D- dimer and thrombocyte levels for severity of COVID-19. Researchers used cross sectional method on 57 COVID-19 patients at the private hospital in Surakarta on the period June to September 2021. Data were taken using total sampling with patients who fulfil the criteria and using Spearman test to analyse the association between D-dimer and platelet levels on the severity COVID-19. The characteristics of the respondents studied were an average age was 57 years, male is more dominant than female with a total of 35 (61.4%), the average severity of respondents was seriously ill (with an average oxygen saturations of 89.39%), the dominant D-dimer level of the respondent is increased with an average of 1699.4 ng/ml, and the dominant platelet level of the respondent was normal with an average of 281.360/Âµl. Results of the analysis with spearman test obtained significance (p-value) 0.560 for the association between D-dimer and severity of COVID-19, while for the association between platelets and severity of COVID-19, significance (p-value) 0.475 were obtained. From the results can be drawn the conclusion there is no association between D-dimer or platelet levels on the severity of COVID-19 disease.Â